Is Teaching Method Still Necessary for Today’s ELT? Evidence from Indonesian English Lecturers - Mobit (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2020)
Drawing on data from a questionnaire and semi-structure interview, this case study investigates the Indonesia English lecturers’ perception toward teaching method and their personal experiences in implementing the methods in the teaching practice as well. Findings report that 89% of the participants keep implementing some methods which fit to the material. It is still reasonable to use in teaching practice since the methods could be aids to drive the teaching process in the classroom. The empirical evidence suggests that in the context of English foreign language teaching, the methods are highly believed as principle guiding points of teaching practices. The participants also argue that the teaching methods have facilitated and supported the lecturers elaborate such material and the ways to teach in real pedagogical activties. Furthermore, it can favor the lecturers in teaching to drive the classroom teaching activities run well.